Optical and Photocatalytic properties of Mn‐doped CuO nanosheets prepared by hydrothermal method. Issue 1 (3rd August 2015) - Jiang, Tingting; Kong, Junhan; Wang, Yongqian; Meng, Dawei; Wang, Dagui; Yu, Meihua
Abstract : Mn‐doped CuO nanosheets can significantly enhance absorption activity both in UV and visible light region in comparision to commercial CuO powder. This paper presents another possibility in the field of photocatalytic degradation of organic pollutants. The mechanism for the enhanced visible‐light‐responsive of Mn‐doped CuO photocatalysts is proposed. Abstract : Mn‐doped CuO nanosheets were prepared through a hydrothermal method to enhance their photocatalytic property. The structural and morphological features were monitored by using X‐Ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) with energy dispersive spectroscopy (EDS). UV‐vis absorption spectra showed the enhance absorption performance both in UV and visible light region. The band gaps were also calculate and the minimum value was 1.25 eV. The photocatalytic activity was investigated by the degradation of methylene blue (MB), which indicated that the photoactivity of samples depended on the amount of Mn 2+ incorporated into the CuO lattice. The improved performance of photocatalysts can be attributed to enhanced light absorption and lower electron‐hole recombination.